A Study on some modified Classical Ciphers for Secure Crypto-System (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Classical Cryptography in the ancient times is a way for secure communication without Computer technology. Developments in the research and technology provide secure communications so as to make the Cryptanalysis difficult. Several Classical algorithms [1] explain the secure cryptosystems for maintaining Confidentiality and difficulty in the process of Cryptanalysis. In this paper we proposed a modified multiple encryption scheme over Classical Ciphers, affine and Caesar Ciphers for secure communications.